Kesejahteraan Psikologis pada Pasien Kanker - I Wayan Candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2015)
This research aim to know the level of psychological well-being of cancer patients in Wangaya General Hospital Denpasar. Type of this research is a descriptive research. This research use cross sectional method. This research use purposive sampling technique. Sample of this research is 23 respondents. The result showed that 17 respondents (73,9 %) have a high level of psychological well-being, and 6 respondents (26,1%) have middle level of psychological well-being.